The Effect of Jabon Veneer Quality on Laminated Veneer Lumber Glue Bond and Bending Strength - Istie Rahayu; Wayan Darmawan; Naresworo Nugroho; Remy Marchal (Jurnal Ilmu dan Teknologi Kayu Tropis, 2015)
Jabon (Anthocephalus cadamba) is a fast  growing wood species widely planted by community in Indonesia. Jabon has large percentage of juvenile wood which affect its veneer quality. This research objective were to determine the effects of wood juvenility and pretreatment on lathe checks, surface roughness and contact angle of the 3.00 mm rotary-cut jabon veneer and to analyze the impact of lathe checks frequency on the LVL glue bond and bending strength.  Jabon logs were subjected to boiling in 75 °C water for4 h. Then they were peeled to produce 3.00 mm veneers in thickness. Frequency, length and depth of lathe checks were measured per 10 cm veneer length by using optical microscope.  Laminated  veneer lumber  (20x20x500) mm3   were made from  7-ply of jabon veneers by using Poly Vinyl Acetate (PVAc) as adhesive.  Glue bond strength and bending strength were measured by UTM Instron.   The results showed lathe check (frequency, length and depth), surface roughness and contact angle were influenced by juvenility. Glue bond strength, Modulus of Elasticity (MOE) and Modulus of Rupture (MOR) of jabon LVL decreased as frequency of lathe check increased.